TERRORISM: THE PROBLEM OF DEFINITION AND WHY? - Onebamhoi Obakhedo, Neville; Unufe, Joseph (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
The concept of terrorism is a victim of definitional pluralism which is fraught with variegated opinions. Variants of terrorism such as the terrorism perpetrated by nation-states or those terrorist acts committed by non-state actors and organizations sponsored and encouraged by governments equally suffer the same fate. As a result of the definitional crisis, individuals, scholars, groups, nation-states and multi-lateral organizations have attempted to define the concept from their perspective. Most of the definitions had sparked-off intellectual controversies and stimulated sentimental reactions. The objective of this paper therefore is to examine the various definitions of terrorism and the controversies they have generated and why the problem of a consensual definition. To be able to achieve the objective of therefore, the secondary data gathering method is deployed to gather information from existing literature, local and international magazines as well as news reportage on the electronic and print media. The paper concludes by arguing that the lack of definitional consensus is traceable to unresolved national, international and ideological issues that have socio-economic and political implications and the barrage of obstacles to achieving or realizing age-long individual or group dreams which are not usually captured in existing definitions. The paper recommends that unless these issues are resolved through accommodation and politics of inclusion, the search for a consensual definition of terrorism would remain elusive.